Implementation of the Function for User Program Execution Control in the Windows Environments - Ju, Jang Senng (IJRDO -Journal of Computer Science Engineering, 2016)
In this paper, we design a program that controls the execution permissions for the running application in the Windows system environment. Itdoes not allow general users to execute the program converting the specific location information of the execution program, to any of the bitvalues with the formal structure information in window program. The converted bit value can be returned to the original bit value in the case ofan authorized user, so that the original program can be normally performed. By doing so, it can be more safely used in the risk of reverseengineering for Windows executable program. We implemented the control program for the program execution authority we proposed in thispaper, and the experiment was performed. At the results of experiments, it was confirmed that the control function to permit execution for theuser program was working properly in the Windows environment.